2002
DOI: 10.1007/s11738-002-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between jasmonates and auxin in regulation of some physiological processes in higher plants

Abstract: Growth and development of plants are regulated by interactions among different plant growth substances. During stress conditions, both abiotic and biotic, interaction of the some hormones activates defense responses. The present review describes the interaction between j asmonates and auxin in regulation of some physiological processes in plant growth and development. Some jasmonate-induced processes reduced by auxins and some auxin stimulated physiological processes inhibited by jasmonates are the focus of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…This provides an explanation that the mechanism of flower inhibition by auxin is dependent on JAMe. Indeed, the interdependent action of both hormones in the regulation of other physiological processes was also observed during root, stamen, and filament growth [32,53,54]. This work confirms that InJMT involved in JAs metabolism in I. nil demonstrates a high homology to genes identified in other plant species.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This provides an explanation that the mechanism of flower inhibition by auxin is dependent on JAMe. Indeed, the interdependent action of both hormones in the regulation of other physiological processes was also observed during root, stamen, and filament growth [32,53,54]. This work confirms that InJMT involved in JAs metabolism in I. nil demonstrates a high homology to genes identified in other plant species.…”
Section: Discussionsupporting
confidence: 75%
“…Many studies provide a great significance of interactions between IAA and JAs, for instance, stem cell growth, abscission, secondary abscission zone formation, tendril coiling, and wounding [32]. In A. thaliana, JAMe inhibits primary root elongation via stimulation of YUC8 and YUC9 expression involved in auxin biosynthesis [33].…”
Section: Introductionmentioning
confidence: 99%
“…IAA generally is considered an antagonist of JA, and it can suppress the induction of defensive compounds such as protease inhibitors and nicotine (Baldwin et al 1997;Saniewski et al 2002). Generally, IAA decreases in response to wounding (Thornburg andLi 1991, Schmelz et al 2003b), however, it rapidly and significantly increased in maize stems in response to ECB herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…a fast one within a few hours, and slow one after several days (Maksymiec et al 2005) may be the reason of the usually observed fast decrease in growth processes and senescence intensification of plants after prolonged exposure to the heavy metals. This conclusion resulted from the observation that, although jasmonates are signal molecules of increased resistance to stress, their activity is also connected with slowing down the activity of the photosynthetic apparatus (Ivanov and Kicheva 1993; Maksymiec and Krupa 2002a) and growth (Irving et al 1999;Saniewski et al 2002;Ś wiątek et al 2002;Merkouropoulos and Shirsat 2003;Maciejewska and Kopcewicz 2003), or acceleration of senescence processes (He et al 2002;Maksymiec and Krupa 2002a). The recently obtained data indicate that for JA-mediated root growth, senescence and defense response, the COI1 gene (encoding proteins which form a part of SCF COI1 -type complex) is needed, and riboflavin for their suppression (Xiao et al 2004).…”
Section: Connections With Hormone Signaling Pathwaysmentioning
confidence: 99%